Aktuální problémy pedagogiky ve výzkumech studentů doktorských studijních programů XIX: Výzvy pedagogického výzkumu v době síťování a nastupující umělé inteligence. Recenzovaný sborník... - Miková Jana, Chráska Miroslav, Kantorová Jana (eds.) (Palacký University Olomouc, 2024)
The reviewed proceedings present 21 contributions from the international conference'Current Issues of Education in Ph.D. Students'Researches XIX: Challenges of Pedagogical Research in the Age of Networking and Emerging Artificial Intelligence', held at the Faculty of Education, Palacký University Olomouc on November 7-8, 2023. The contributions are focused on the field of education - namely the issue of personality of a teacher, didactic questions, psychological aspects of education and other actual issues.